Under control: how a dietary additive can restore the gut microbiome and proteomic profile, and improve disease resilience in a marine teleostean fish fed vegetable diets - María Carla Piazzon; Josep Alvar Calduch-Giner; Belén Fouz; Itziar Estensoro; Paula Simó-Mirabet; Mónica Puyalto; Vasileios Karalazos; Oswaldo Palenzuela; Ariadna Sitjà-Bobadilla; Jaume Pérez-Sánchez (Microbiome, 2017)
Abstract Background The constant increase of aquaculture production and wealthy seafood consumption has forced the industry to explore alternative and more sustainable raw aquafeed materials, and plant ingredients have been used to replace marine feedstuffs in many farmed fish. The objective of the present study was to assess whether plant-based diets can induce changes in the intestinal mucus proteome, gut autochthonous microbiota and disease susceptibility of fish, and whether these changes could be reversed by the addition of sodium butyrate to the diets. Three different trials were performed using the teleostean gilthead sea bream (Sparus aurata) as model. In a first preliminary short-term trial, fish were fed with the additive (0.8%) supplementing a basal diet with low vegetable inclusion (D1) and then challenged with a bacteria to detect possible effects on survival. In a second trial, fish were fed with diets with greater vegetable inclusion levels (D2, D3) and the long-term effect of sodium butyrate at a lower dose (0.4%) added to D3 (D4 diet) was tested on the intestinal proteome and microbiome. In a third trial, the long-term effectiveness of sodium butyrate (D4) to prevent disease outcome after an intestinal parasite (Enteromyxum leei) challenge was tested. Results The results showed that opposed forces were driven by dietary plant ingredients and sodium butyrate supplementation in fish diet. On the one hand, vegetable diets induced high parasite infection levels that provoked drops in growth performance, decreased intestinal microbiota diversity, induced the dominance of the Photobacterium genus, as well as altered the gut mucosal proteome suggesting detrimental effects on intestinal function. On the other hand, butyrate addition slightly decreased cumulative mortality after bacterial challenge, avoided growth retardation in parasitized fish, increased intestinal microbiota diversity with a higher representation of butyrate-producing bacteria and reversed most vegetable diet-induced changes in the gut proteome. Conclusions This integrative work gives insights on the pleiotropic effects of a dietary additive on the restoration of intestinal homeostasis and disease resilience, using a multifaceted approach.